A. \(m \in \left( { - 3; + \infty } \right)\)
B. \(m \in \left( { - \infty ; - 3} \right] \cup \left[ {2; + \infty } \right)\)
C. \(m \in \left( { - \infty ; - 3} \right)\)
D. \(m \in \left( { - 3;1} \right] \cup \left[ {2; + \infty } \right)\)
C
Đặt \(t = \cos x\), với \(x \in \left( {0;\frac{\pi }{3}} \right) \to t \in \left( {\frac{1}{2};1} \right)\).
Hàm số trở thành \(y\left( t \right) = \frac{{2t + 3}}{{2t - m}} \to y'\left( t \right) = \frac{{ - 2m - 6}}{{{{\left( {2t - m} \right)}^2}}}\).
Ta có \(t' = - \sin x < 0,{\rm{ }}\forall x \in \left( {0;\frac{\pi }{3}} \right)\), do đó \(t = \cos x\) nghịch biến trên \(\left( {0;\frac{\pi }{3}} \right).\)
Do đó YCBT \( \leftrightarrow y\left( t \right)\) đồng biến trên khoảng \(\left( {\frac{1}{2};1} \right)\)\( \leftrightarrow y'\left( t \right) > 0,\,\,\forall t \in \left( {\frac{1}{2};1} \right)\)
\( \Leftrightarrow \left\{ \begin{array}{l}
- 2m - 6 > 0\\
2t - m \ne 0
\end{array} \right.,\,\,\forall t \in \left( {\frac{1}{2};1} \right) \Leftrightarrow \left\{ \begin{array}{l}
m < - 3\\
m \ne 2t
\end{array} \right.,\,\,\forall t \in \left( {\frac{1}{2};1} \right) \Leftrightarrow \left\{ \begin{array}{l}
m < - 3\\
m \notin \left( {1;2} \right)
\end{array} \right. \Leftrightarrow m < - 3.\)
Nhận xét. Do \(t \in \left( {\frac{1}{2};1} \right) \to 2t \in \left( {1;2} \right)\). Và \(m \notin \left( {1;2} \right) \leftrightarrow \left[ \begin{array}{l}
m \le 1\\
m \ge 2
\end{array} \right.\) .
Câu hỏi trên thuộc đề trắc nghiệm dưới đây !
Copyright © 2021 HOCTAP247